2017
DOI: 10.1371/journal.pone.0174150
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the genetic diversity and population structure of yam (Dioscorea alata L.) using microsatellite markers

Abstract: Yams (Dioscorea sp.) are staple food crops for millions of people in tropical and subtropical regions. Dioscorea alata, also known as greater yam, is one of the major cultivated species and most widely distributed throughout the tropics. Despite its economic and cultural importance, very little is known about its origin, diversity and genetics. As a consequence, breeding efforts for resistance to its main disease, anthracnose, have been fairly limited. The objective of this study was to contribute to the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 44 publications
3
56
2
Order By: Relevance
“…Our validation panel was thus representative of the worldwide D. alata diversity.Moreover, a good correlation was obtained between the findings of the previous study of worldwide D. alata diversity ofArnau et al (2017) and the gene pools identified in this study (Appendix B). Our validation panel was thus representative of the worldwide D. alata diversity.Moreover, a good correlation was obtained between the findings of the previous study of worldwide D. alata diversity ofArnau et al (2017) and the gene pools identified in this study (Appendix B).…”
supporting
confidence: 84%
See 4 more Smart Citations
“…Our validation panel was thus representative of the worldwide D. alata diversity.Moreover, a good correlation was obtained between the findings of the previous study of worldwide D. alata diversity ofArnau et al (2017) and the gene pools identified in this study (Appendix B). Our validation panel was thus representative of the worldwide D. alata diversity.Moreover, a good correlation was obtained between the findings of the previous study of worldwide D. alata diversity ofArnau et al (2017) and the gene pools identified in this study (Appendix B).…”
supporting
confidence: 84%
“…Nodes shape and letter, cluster of diversity identified by a bootstrap procedure; red nodes, diploids; green nodes, triploids; blue nodes, tetraploids; edge colors, similarity from gray (0.64) to black (1) with previous genetic diversity studies that already pooled these accessions together and highlighted this intragroup variability in tubers (Arnau et al, 2017;Malapa et al, 2005). Nodes shape and letter, cluster of diversity identified by a bootstrap procedure; red nodes, diploids; green nodes, triploids; blue nodes, tetraploids; edge colors, similarity from gray (0.64) to black (1) with previous genetic diversity studies that already pooled these accessions together and highlighted this intragroup variability in tubers (Arnau et al, 2017;Malapa et al, 2005).…”
Section: Assessment Of Allelic Dosage and Detection Of Ploidy Levelsmentioning
confidence: 94%
See 3 more Smart Citations